Efficacy and safety of elbasvir/grazoprevir in participants with hepatitis C virus genotype 1, 4, or 6 infection from the Asia–Pacific region and Russia: Final results from the randomized C‐CORAL study. Issue 1 (9th December 2018) - Wei, Lai; Jia, Ji Dong; Wang, Fu Sheng; Niu, Jun Qi; Zhao, Xu Min; Mu, Shengmei; Liang, Li Wen; Wang, Zaiqi; Hwang, Peggy; Robertson, Michael N; Ingravallo, Paul; Asante‐Appiah, Ernest; et al.
Abstract: Background and Aim: Although treatment with direct‐acting antivirals has dramatically improved morbidity and mortality attributable to chronic hepatitis C virus infection, universal access to these medicines has been slow in the Asia–Pacific region and Russia. This study evaluated efficacy and safety of elbasvir/grazoprevir in participants with hepatitis C virus infection from Asia–Pacific countries and Russia (C‐CORAL). Methods: C‐CORAL was a phase 3, randomized, placebo‐controlled study (NCT02251990). Treatment‐naive, HIV‐negative, cirrhotic and non‐cirrhotic participants with chronic hepatitis C genotype 1, 4, or 6 infection were randomized to elbasvir 50 mg/grazoprevir 100 mg once daily for 12 weeks (immediate‐treatment group) or placebo followed by deferred treatment with elbasvir/grazoprevir (deferred‐treatment group). The primary efficacy outcome was sustained virologic response at 12 weeks, and the primary safety outcome was a comparison between the immediate‐treatment group and placebo phase of the deferred‐treatment group. Results: A total of 489 participants were randomized (immediate‐treatment group, n  = 366; deferred‐treatment group, n  = 123). Sustained virologic response at 12 weeks in the combined immediate/deferred‐treatment groups was 94.4% (459/486; 95% confidence interval = 92.4–96.5%). Sustained virologic response at 12 weeks was 98.2% in participants with genotype 1b, 91.9% with genotype 1a, and 66.7% with genotype 6 infection. Similar rates of adverse events and drug‐related adverse events were seen in the immediate‐treatment group versus placebo phase of the deferred‐treatment group (51.0% vs 50.4% and 21.4% vs 21.1%). Conclusions: Elbasvir/grazoprevir for 12 weeks represents an effective and well‐tolerated treatment option for treatment‐naive people with genotype 1 infection from Asia–Pacific countries and Russia.